Chiral fluorescent sensor based on H8-BINOL for the high enantioselective recognition of d- and l-phenylalanine. Issue 19 (19th April 2022) - Zhang, Yafeng; Wang, Huizhen; Yu, Hu; Sun, Xiaoxia
Abstract : A triazole-modified H8 -BINOL fluorescence sensor was synthesized with 95% yield, which can enantioselectively recognize l -phenylalanine without the participation of metal ions, even the enantioselective fluorescence enhancement ratio was up to 104.28. Abstract : Phenylalanine an essential aromatic amino acid for humans and animals, cannot be synthesized by humans and animals on their own. However, it synthesizes important neurotransmitters and hormones in the body and is involved in gluconeogenesis and lipid metabolism. Moreover, the two opposite configurations of phenylalanine have different activities. For example, l -phenylalanine is a biologically active optical isomer involved in crucial biological processes, the lack of which will lead to intellectual disability, while d -phenylalanine only acts as a chiral intermediate. In this research, an H8 -BINOL chiral fluorescent sensor modified with 1, 2, 3-triazole was synthesized in high yield (95%) by nucleophilic substitution and click reaction. The chiral fluorescent sensor showed high enantioselectivity toward phenylalanine. l -Phenylalanine enhanced the fluorescence response of the probe significantly, while d -phenylalanine had no obvious fluorescence response change. The enantioselective fluorescence enhancement ratio [ef = ( I L − I 0 )/( I D − I 0 ), where I 0 is the fluorescence of the sensor without amino acids] for the highest fluorescence intensity at 20.0 equivalents of amino acids was 104.48. In this way, the probe could be used to identify and differentiate different configurations of phenylalanine.